PASSIVE CONSTRUCTION OF ACEHNESE LANGUAGE: X-BAR ANALYSIS - Rostina Taib; Mulyadi Mulyadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to analyze the passive construction in Acehnese Language (AL) by using X- Bar Theory which utilized the oral, written, and the data created by the researcher as the native speaker. This research was conducted in the area of Aceh Besar, Aceh Pidie, and Aceh Utara. There were 12 informants selected and the data were taken orally, and in a written manner. The data collection was conducted through recording technique and note taking technique. After collecting the data, the researcher applied introspection technique through elicitation technique.  The result of this research exhibits that the passive construction in Acehnese Language is in the form of syntactical passive. There is no morphological passive form discovered in this language because there is no marker found in the verb as the passive marker morphologically. Besides that, verb in Acehnese Language is aligned with subject as the agent of an action in the active construction. In the passive construction, the verb must agree with the action which functions as the complementary. In order to determine the passive construction in this language, the constituents in the sentence must be viewed holistically. The only one passive marker that can be identified is the preposition of le ‘by’. Based on the X-Bar analysis conducted to show the passive construction in Acehnese Language it is found that specifier, complement, and adverb play important roles to construct it. Specifier is an internal structure that is required to be positioned by NP, and is combined to become I’ and form IP.